Community engagement in higher education: Developments after the first institutional audit cycle - Mohale, M. A. (South African Journal of Higher Education, 2023)
This study explores how three universities have responded to the Higher Education Qualifications Committee (HEQC) recommendations regarding deficiencies in implementing their community engagement (CE) missions. The Education White Paper 3 locates community engagement within the policy changes of transformation in higher education. However, literature reveals that there is still considerable resistance to accepting CE as a core function of universities. This study is qualitative and uses document analysis to understand the extent to which three universities identified for this study have progressed regarding their CE missions. The documents analysed include HEQC first audit cycle reports, policies, strategic plans, annual reports and institutional websites. Open Systems Theory (Emery) was used to underpin the findings of this study. The results revealed that despite the challenges reported in the literature, universities had developed policy frameworks to facilitate understanding of the concept among internal stakeholders and put structures for managing CE initiatives.